A novel invariant-based design approach to carbon fiber reinforced laminates. (1st January 2017) - Melo, Jose Daniel D.; Bi, Jing; Tsai, Stephen W.
Abstract: An invariant-based design procedure using trace-normalized plane stress stiffness matrix and unit circle failure criterion for carbon fiber reinforced polymer (CFRP) is presented and compared to the traditional design approach. Using the invariant-based design approach, the optimal stiffness-based layup solution is material independent and thus valid for any CFRP. Then, trace of the plane stress stiffness matrix is the only material property needed for strain scaling. Moreover, the unit circle failure criterion is invariant with respect to ply orientation and requires only the unidirectional longitudinal tensile and compressive strains-to-failure, which greatly simplifies testing. In this study, smooth and open-hole plates are evaluated using the traditional design approach and invariant-based design procedures. The results show that the invariant-based design approach greatly simplifies the design procedure of CFRP structural components.